End User Satisfaction for Location Health Service Application with Analysis of Task Technology Fit - Wanti, Linda Perdana; Insan, Hijriah Fajar Muhammad; Prasetya, Nur Wachid Adi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2020)
There are several types of health services that provide information about health care facilities, such as pharmacies, health centers, clinics, and hospitals. Application of health service facilities location is used to facilitate users in reaching the nearest health service facility. The application of the health care facilities location has not been optimally used by the user so often. The advantage of analyzing the system is to determine its direct and indirect effect on the end-user. This research analyzes task technology fit (TTF) of application for the location of health service facilities based on measures of end-user satisfaction and knowledge management system (KMS). The research began with an exploratory study through interviews with users of health service applications. With the results of interviews, the research hypothesis model was built to integrate health service applications with the task technology fit model based on end-user satisfaction . The results obtained from this study are the impact of the performance of a good application system can increase end-user satisfaction in optimizing all the modules that exist in the application. The intended system performance is the quality of information presented by the application including the location of the health service facility and the accuracy of information needed by the end which affects the compatibility of the health service facility application which significantly increase the end-user satisfaction, and this will automatically affect the TTF performance for the better. This needs to be responded to so that the application continues to be updated in real-time to continue to provide information about the application in accordance with the development and needs of end-users.  This linkage shows that the role of task technology fit has a good impact on system development that affects system relationships and end-user satisfaction in applications.